Manajemen Sumber Daya Manusia Anak Panti Asuhan: Strategi Pemberdayaan Menuju Kemandirian dan Daya Saing Sosial - Rastina Kalla; Tenriwaru; Muh. Haerdiansyah Syahnur (Fakultas Ekonomi, Universitas Muslim Indonesia, 2026)
Human resource management (HRM) in orphanages plays a crucial role in fostering children’s independence and social competitiveness. This study aims to analyze HRM practices and empowerment strategies implemented to support the capacity development of children living in orphanages. The research adopts a descriptive qualitative approach, with data collected through interviews, observation, and documentation. The informants consist of orphanage managers, caregivers, and foster children. The findings indicate that HRM is implemented through structured developmental planning, skill development programs, and continuous evaluation oriented toward character building and self-reliance. Empowerment strategies are carried out through formal and non-formal education, life-skills training, social value development, and the strengthening of social networks. The application of structured and empowerment-based HRM contributes positively to enhancing the independence and social competitiveness of foster children. This study provides practical implications for orphanage administrators in designing sustainable human resource management models.